621.383 RESEARCH OF MECHANICAL PART OF SOLAR PHOTOVOLTAIC POWER STATION - Sodiqov, Timur (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In dusty atmospheric conditions, various dust particles settle on their surface, which, depending on their thickness, damage the tempered glass, reduce the service life of the panels, and also prevent photovoltaic elements from receiving more sunlight, as a result, their temperature increases, the output power, short-circuit current and, therefore, the efficiency factor decrease by up to 50%. Therefore, in order to increase the efficiency and maintain the operability of solar panels, it is considered important to examine the solar panels of solar photovoltaic stations for dustiness This article considers a photovoltaic station, which was built first on the territory of Uzbekistan. This station, with a capacity of 130 kW, was launched in test mode so that test modern four type of solar in the natural and climate conditions of Uzbekistan, train personnel in the field of solar energy, improve skills in the operation of photovoltaic station, as well as to identify practical conclusions on the basis of which in the future to choose the most effective solutions It was determined that with a contaminated optical area, as well as the absence of cooling and orientation mechanisms, short circuit current of a 250 W solar panel deviates on average from the rated value by almost 27 %, and after cleaning the deviation is 12,85 %, which means that it is possible to increase short circuit current by an average of 10-15 % by regularly cleaning the surface, thereby increasing the generation of the solar power stations itself.